2009
DOI: 10.1021/cr0782832
|View full text |Cite
|
Sign up to set email alerts
|

Plant Orthoesters

Abstract: Chart 2. Structures of 1-Alkyldaphnanes (81-109), Resiniferonoids (110-113), Genkwanines (114-122), and Rediocides (123-129)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
134
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(138 citation statements)
references
References 294 publications
2
134
0
2
Order By: Relevance
“…[10][11][12] The HMBC correlations from a downfield signal at d suggesting the orthoester moiety in 1 is an isobutylate group, rarely encountered in phragmalin orthoesters. 2,16) A proton signal at d H 3.28, no correlation with carbon observed in HSQC spectrum, showed HMBC correlations with carbon signals at d C 84.6 (C-1), d C 48.2 (C-10), and d C 40.3 (C-29), which suggested that it is a hydroxy proton singal and attached at C-1. The presence of the OH group at C-1, the weak HMBC correlation from H-30 (d H 4.51) to the orthoester carbon, and the chemical shifts of C-2 (d C 75.2), C-8 (d C 83.8), C-9 (d C 85.4) and C-30 (d C 78.0) confined the location of the orthoester group to C-8/C-9/C-30.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…[10][11][12] The HMBC correlations from a downfield signal at d suggesting the orthoester moiety in 1 is an isobutylate group, rarely encountered in phragmalin orthoesters. 2,16) A proton signal at d H 3.28, no correlation with carbon observed in HSQC spectrum, showed HMBC correlations with carbon signals at d C 84.6 (C-1), d C 48.2 (C-10), and d C 40.3 (C-29), which suggested that it is a hydroxy proton singal and attached at C-1. The presence of the OH group at C-1, the weak HMBC correlation from H-30 (d H 4.51) to the orthoester carbon, and the chemical shifts of C-2 (d C 75.2), C-8 (d C 83.8), C-9 (d C 85.4) and C-30 (d C 78.0) confined the location of the orthoester group to C-8/C-9/C-30.…”
Section: Resultsmentioning
confidence: 91%
“…1) Phragmalin-type limonoid orthoester is an important branch of orthoesters with phragmalin limonoid as the basic skeleton, discovered exclusively from the genera of Meliaceae. 1,2) The genus chukrasia (Meliaceae) 3) was revealed to be a rich resource of structure diversified phragmalin-type limonoids as well as orthoesters. [4][5][6][7][8][9] Our previous study on phragmalin-type limonoids from Chukrasia tabularis var.…”
mentioning
confidence: 99%
“…[1][2][3] Daphnane is a major class of diterpenes and has received considerable attention due to its important pharmacological activity. [4][5][6] Resiniferatoxin (1, Fig. 1), a representative daphnane diterpene, is the irritant in the latex of Euphorbia resinifera.…”
Section: Introductionmentioning
confidence: 99%
“…Keywords daphnane; diterpenoid; (+)-resiniferatoxin; total synthesis; synthetic methodology 1 引言 瑞香烷型二萜类天然产物主要分布在瑞香科和大 戟科植物中, 具有 5/7/6 三环骨架 1, 通常在 C3、C4、 C5、C9、C13、C14、C20 位置有羟基, 在 C9、C13、 C14 具有特定的原酸酯结构. 根据 B 环和 C 环的氧化形 式以及 A 环的取代形式, 可将已知的瑞香烷型二萜天然 产物(图 1)分为六类 [1] : daphnetoxins 2、12-hydroxydaphnetoxins 3、1-alkyldaphnanes 4、resiniferonoids 5、 genkwanines 6 和 rediocides 7; 其中, daphnetoxins 通常 在 A 环具有 α-β 不饱和酮结构, 且 B 环具有 C5β 羟基、 C20 羟基、C6α-C7α 环氧结构; 12-hydroxydaphnetoxins 相对于 daphnetoxins 在 C12 处多一个含氧官能团 OR, 并 且 OR 通常为酰氧基; 1-alkyldaphnanes 通常具有饱和的 A 环, 并且原酸酯烷基链末端和 A 环 C1 之间具有一个 大环; resiniferonoids 相对于 daphnetoxins 而言, A 环具有 α-β 不饱和酮结构, B 环 C5 为亚甲基且 C6-C7 之间为双 键, C20 为羟基或者酰氧基; genkwanines 通常在 B 环 C6-C7 之间具有双羟基, 并且饱和 A 环 C3 以及 B 环 C20 …”
unclassified
“…根据 B 环和 C 环的氧化形 式以及 A 环的取代形式, 可将已知的瑞香烷型二萜天然 产物(图 1)分为六类 [1] : daphnetoxins 2、12-hydroxydaphnetoxins 3、1-alkyldaphnanes 4、resiniferonoids 5、 genkwanines 6 和 rediocides 7; 其中, daphnetoxins 通常 图 1 瑞香烷型二萜骨架 Figure 1 The skeleton of daphnane-type diterpenoids 也为羟基; rediocides 通常在 C3 和 C16 之间具有 12 个碳 的大环内酯结构, 并且具有特殊的 C9、C12、C14 原酸 酯结构而不是常见的 C9、C13、C14 原酸酯结构; 另外, 一些虎皮楠生物碱也具备瑞香烷骨架和断裂的瑞香烷 骨架, 例如 8 和 9. 至今, 已经有 100 多个瑞香烷型二萜 类天然产物得到分离、鉴定, 它们在抗 HIV、抗癌、抗 白血病、亲神经性、杀虫、细胞毒性方面显示很好的生 物活性 [2] .…”
unclassified